Fevipiprant has a low risk of influencing co-medication pharmacokinetics: Impact on simvastatin and rosuvastatin in different SLCO1B1 genotypes. (August 2019) - Poller, Birk; Woessner, Ralph; Barve, Avantika; Tillmann, Hanns-Christian; Vemula, Janardhana; Nica, Alexandra; Elbast, Walid; Schiller, Hilmar; End, Peter; Camenisch, Gian; Weiss, Markus
Abstract: Fevipiprant, a prostaglandin D2 receptor 2 antagonist, is in clinical development as a treatment for asthma. The goal of this study was to assess the potential of fevipiprant to cause drug-drug interactions (DDI) as a perpetrator, that is, by altering the pharmacokinetics (PK) of co-medications. In vitro drug interaction studies of clinically relevant drug metabolizing enzymes and transporters were conducted for fevipiprant and its acyl glucuronide (AG) metabolite. Comparison of Ki values with unbound systemic or portal vein steady-state plasma exposure of fevipiprant and its AG metabolite revealed the potential for inhibition of organic anion transporting polypeptide 1B1 (OATP1B1) transporters (R-value of 5.99), while other targets including cytochrome P450 enzymes were not, or only marginally, inhibited. Consequently, an open-label, two-part, two-period, single-sequence clinical study assessed the effect of fevipiprant 450 mg QD on the pharmacokinetics of simvastatin 20 mg and rosuvastatin 20 mg, two statins with different dependency in OATP1B1-mediated hepatic uptake, in healthy adult volunteers. The study also assessed the pharmacogenetics of the SLCO1B1 gene, which encodes OATP1B1. Clinically, fevipiprant 450 mg QD showed a low potential for interaction and increased the peak concentrations of simvastatin acid and rosuvastatin by 2.23- and 1.87-fold, respectively, with little or no impact on total exposure. Genotype analysis confirmed that SLCO1B1 genotype influences statin pharmacokinetics to a similar extent either with or without fevipiprant co-administration. In summary, fevipiprant at 450 mg QD has only minor liabilities as a perpetrator for DDI.